Computationally-efficient aeroelastic analysis tool for short-wing/propeller configuration on compound helicopters - Wang, Zi; Popov, Atanas A. (2018)
A time-domain aeroelastic analysis for short-wing/propeller configuration in compound helicopters is presented in this paper. A linear Timoshenko beam is used in conjunction with analytical aerodynamic theories, while propeller effects are simplified as defined velocity profiles in the advancing and vertical directions. A numerical modal analysis approach is used to incorporate the coupling between bending and torsion. The paper focuses on the application of coupled mode shapes and Timoshenko beam in an aeroelasticity context. A Eurocopter X3-liked short-wing/propeller configuration is studied. Differences introduced by coupled mode shapes and Timoshenko beam theory are discussed. The results show that coupled modal analysis gives a better representation of the modal behaviour with less computational power required. While rotary inertia and shear deformation effects result in a higher mean deflection and a smaller amplitude in the steady state, revealing a different energy distribution mechanism compare to Euler-Bernoulli beam in the system studied.